2001
DOI: 10.1002/zoo.1036
|View full text |Cite
|
Sign up to set email alerts
|

Aggression control in a bachelor herd of fringe‐eared oryx (Oryx gazella callotis), with melengestrol acetate: Behavioral and endocrine observations

Abstract: Aggression control is becoming an important component in the management of animals in captivity, but rigorous quantification of aggressive behavior has heretofore been lacking. This study was done to assess the ability of melengestrol acetate (MGA) given with feed (1.54 mg/kg) to control aggression in a bachelor group of fringe-eared oryx (Oryx gazella callotis). Systematic behavioral observations were conducted and fecal androgen content was measured for 42 and 90 days, respectively, before treatment, and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…However, most research on how each of the two contraceptives used at the DLC affects behavior suggests that each contraceptive lowers rates of aggressive behavior in the subject. For example, in various macaque species Depo Provera is shown to reduce the frequency of aggressive acts [Michael and Zumpe, 1993], and studies of fringe-eared oryx (Oryx gazella callotis), golden-headed lion tamarins (Leontopithecus chrysomelas), Rodrigues fruit bats (Pteropus rodricensis), and Hamadryas baboons (Papio hamadryas) have all shown that melengestrol acetate (MGA) results in either no significant change or a significant decrease in aggressive behavior [Portugal, 1995;Hayes, 1996;De Vleeschouwer et al, 2000;Patton et al, 2001]. If the contraceptives affect the two species in the study similarly, the data presented in this study may actually underestimate the degree of aggressive behavior typically displayed by females.…”
Section: Contraceptivesmentioning
confidence: 98%
“…However, most research on how each of the two contraceptives used at the DLC affects behavior suggests that each contraceptive lowers rates of aggressive behavior in the subject. For example, in various macaque species Depo Provera is shown to reduce the frequency of aggressive acts [Michael and Zumpe, 1993], and studies of fringe-eared oryx (Oryx gazella callotis), golden-headed lion tamarins (Leontopithecus chrysomelas), Rodrigues fruit bats (Pteropus rodricensis), and Hamadryas baboons (Papio hamadryas) have all shown that melengestrol acetate (MGA) results in either no significant change or a significant decrease in aggressive behavior [Portugal, 1995;Hayes, 1996;De Vleeschouwer et al, 2000;Patton et al, 2001]. If the contraceptives affect the two species in the study similarly, the data presented in this study may actually underestimate the degree of aggressive behavior typically displayed by females.…”
Section: Contraceptivesmentioning
confidence: 98%
“…Inter-assay coefficient of variation was o6%. The protocols and performance of radioimmunoassays to measure progestin and androgen metabolite concentrations in the same samples of feces are described in Patton et al (1999Patton et al ( , 2001, respectively.…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Castration of domestic animals can reduce aggressive interactions between conspecifics and humans [Martin and Lindsay, 1998]. However, although manipulating testosterone concentrations has modified aggressive behavior in some species [Martin and Lindsay, 1998;Norton et al, 2000], including fringe-eared oryx [Patton et al, 2001], the influence of testosterone on aggressive behavior is not fully understood.…”
Section: Introductionmentioning
confidence: 98%